Emotional Intelligence and Financial Decision-Making Behavior: An Integrative Psychological Framework - Bakhati, Savyata (DAV Research Journal, 2026)
This paper aims to explore how financial literacy and emotional intelligence (EI) influence financial decision-making. As financial markets become more complex, individuals need to develop the necessary skills to make informed financial choices. This research examines the impact of financial self-efficacy, digital financial literacy, and financial risk tolerance on financial behavior, with EI playing a moderating role. This study employs a quantitative cross-sectional data employing descriptive and causal research design. A structured questionnaire was distributed to 205 university students who have been working to different organizations to assess their financial literacy, emotional intelligence, and financial behaviors. The study utilized a Likert scale to measure responses, and data were analyzed using SPSS and the mediation analysis was conducted by using Hayes Process Macro. The findings reveal a significant relationship between financial literacy and financial behavior. However, individuals with high emotional intelligence demonstrated better financial outcomes regardless of their financial knowledge. Those with high financial literacy but low EI often struggled with impulsive spending, while individuals with moderate financial literacy but high EI exhibited stronger financial discipline. This finding underscores the importance of integrating EI training into financial literacy as well as trainings programs to enhance financial decision-making. Policymakers and educators should incorporate EI development into financial literacy programs to enhance financial well-being.